Analisis Kinerja Persimpangan Kondisi Eksisting (Studi Kasus: Persimpangan Jalan HR. Soebrantas- Jalan Kubang Raya-Jalan Garuda Sakti Pekanbaru) - Prasetia, Bayu Reski; Sandhyavitri, Ari; Djuniati, Sri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
A meeting of two or more roads may rise conflict of traffic flow use defined or an intersection point. The intersection of Jl. HR. Soebrantas–Jl. Kubang Raya-Jl. Garuda Sakti Pekanbaru, was selected as a core study in this paper. This intersection to cause trafffic congestion delays and traffic jams during peak hours. This study used the method of Indonesian Highway Capacity Manual 1997. Data obtained by conducting surveys on traffic volume. The researched was conducted for three days; Friday (13/10/2017), Saturday (4/11/2017), and Monday (6/11/2017). From the survey results and the calculation of peak hour of the traffic flow occurred on Friday 17:15 to 18:15 pm with the value of Q = 4058,6 smp/hour, C = 4217,696 smp/hour, DS = 0,962, DTI = 13,432 det/smp, DTMA = 9,537 det/smp, DTMI = 21,272 det/smp, DG = 4,02 det/smp, D = 17,452, QP% = 37,1-73,3%. Since DS value is greater than the requirement of Indonesian Highway Capacity Manual 1997 which is 0.85, it is necessary to plan alternative solutions to improve the performance of the intersection.Keywords: Jl. HR. Soebrantas-Jl. Kubang Raya-Jl. Garuda Sakti Pekanbaru, Q (Traffic flow), C (Capacity), DS (Degree of saturation).